Berita Calon Kepala Daerah Pada Pilkada Kota Medan 2010 di Harian Waspada - HARAHAP, HUSNUL ISA (Politeia: Jurnal Ilmu Politik, 2015)
It is the study of news regional head candidates in local elections in Kota Medan. Precisely in April 2010 local elections and published by Harian Waspada. The contents of the news pub-lished are that has associated with one of the candidates. This study was conducted with the ap-proach of political communication. Collecting data are using literature and documents. The da-ta analysis with descriptive analysis method. The study found there are variations in the quanti-ty of news regional head candidates. This means that no candidate dominates the news content. This can be seen from the difference in the news every week especially regarding regional head candidates. However there is a regional head candidates very rarely reported. It seems related to the amount of advertising campaigns published in this daily. But the fact it is not related at all to the advertising campaign, although it is almost impossible eliminate their relationship.Keywords: Regional election, candidate, mass media.